Competing with each other: Fish isotopic niche in two resource availability contexts - Pelage, Latifa; Lucena-Frédou, Flávia; Eduardo, Leandro Nole; Le Loc’h, François; Bertrand, Arnaud; Lira, Alex Souza; Frédou, Thierry (Frontiers in Marine Science, 2022)
Introduction Competition embodies species struggle for space and food and is, therefore, a critical evolutionary mechanism influencing species spatiotemporal patterns and persistence. One of the main drivers of competition is resource availability. In marine ecosystems, resource availability is determined, among other things, by habitat structural complexity, as it increases biodiversity and species abundance. In this context, our study aims at understanding how the differences in substrate complexity affect potential trophic competition between demersal fishes in Northeast Brazil. Methods We selected two zones contrasted in terms of substrates, one dominated by sand (zone A) and the other by complex substrates such as reefs and calcareous algae (zone B). We used Stable Isotope Analysis (SIA) to quantify intraspecific and interspecific interactions of demersal fishes in both zones. We compared the competitive interactions between zones using social network analysis (SNA), a suitable method to quantitatively study a set of interactions. Results In the sand-dominated zone, demersal fish showed greater interspecific competition and occupied a larger isotopic niche suggesting that a resource-limited context led to diet diversification in the community. Some species expanded their niche through diet plasticity, while others showed higher intraspecific competition than in Zone B to cope with the greater interspecific competition. Discussion Combining SNA and SIA provided a new method to investigate competition. This study potentially gives a perspective on the future ecological response of the demersal fishes at the community and species level. With habitat degradation and climate change, the complex substrates in zone B will probably disappear gradually, transforming this zone into an ecosystem akin to zone A. This would be detrimental to species more vulnerable to interspecific competition, particularly those targeted by fisheries.